2015
DOI: 10.1111/apt.13292
|View full text |Cite
|
Sign up to set email alerts
|

Novel association between serum pentraxin‐2 levels and advanced fibrosis in well‐characterised patients with non‐alcoholic fatty liver disease

Abstract: SUMMARY BackgroundPentraxin-2 (PTX-2), a serum protein, inhibits inflammation and fibrosis, and recombinant PTX-2 is being tested as an anti-fibrotic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Considering serum biomarkers in NAFLD, either singly or in combination biomarkers may be a surrogate for the presence and degree of hepatic steatosis or steatohepatitis or may be associated with the presence and progression of liver fibrosis. 3,4 In their proof of concept study, Verna et al 5 identified that serum levels of Pentraxin-2 (PTX-2), a serum protein known to inhibit fibrosis in vitro, 6 appears to be significantly associated with both the presence and progression of NAFLD. Verna et al demonstrate a significant association between PTX-2 levels and the presence of NAFLD, with mean PTX-2 levels being significantly lower in patients with NAFLD compared with normal controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering serum biomarkers in NAFLD, either singly or in combination biomarkers may be a surrogate for the presence and degree of hepatic steatosis or steatohepatitis or may be associated with the presence and progression of liver fibrosis. 3,4 In their proof of concept study, Verna et al 5 identified that serum levels of Pentraxin-2 (PTX-2), a serum protein known to inhibit fibrosis in vitro, 6 appears to be significantly associated with both the presence and progression of NAFLD. Verna et al demonstrate a significant association between PTX-2 levels and the presence of NAFLD, with mean PTX-2 levels being significantly lower in patients with NAFLD compared with normal controls.…”
mentioning
confidence: 99%
“…[1][2][3][4] As we demonstrate in a recent issue of Alimentary Pharmacology & Therapeutics, Pentraxin-2 (PTX-2) may represent an incremental step towards the improved diagnostic strategies that could perhaps be used to aid in the screening and staging of this disease, and it may also serve as a therapeutic target for hepatic fibrosis in NAFLD. 5 In their editorial, Donnelly and Simpson make several important points. 6 Although there was no association seen between PTX-2 levels and body mass index (BMI) in this limited cohort, this relationship certainly warrants ongoing investigation in larger studies given the regulation of PTX-2 synthesis by IL-6.…”
mentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementmentioning
confidence: 99%
“…Non‐alcoholic fatty liver disease (NAFLD) remains a crucial focus for novel investigation given its overwhelming prevalence, potential for progression to life‐threatening cirrhosis and current lack of accurate non‐invasive diagnostic tests . As we demonstrate in a recent issue of Alimentary Pharmacology & Therapeutics , Pentraxin‐2 (PTX‐2) may represent an incremental step towards the improved diagnostic strategies that could perhaps be used to aid in the screening and staging of this disease, and it may also serve as a therapeutic target for hepatic fibrosis in NAFLD …”
mentioning
confidence: 99%
“…This in turn promotes epithelial healing and resolution of inflammation and scarring. The constitutive level of production and consumption of PTX-2 at fibrotic sites is thought to result in the lower circulating levels of PTX-2 in fibrotic disease, as seen in IPF [8], end-stage renal disease [8] and nonalcoholic steatohepatitis [10].…”
Section: Introductionmentioning
confidence: 99%